Diet halalan toyyiban: porcine blood plasms detection in chicken meatball by conventional polymerase chain reaction (PCR) analysis - Ismail, Norfadzilah; Abd Mutalib, Sahilah; Mohd Kashim, Mohd Izhar Ariff; Mohd Khalid, Rozida; Sedek, Razalee; Ariffin, Ahmad Azuhairi (Centre for Contemporary Fiqh and Shariah Compliance, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2018)
The addition of blood plasm in meatballs become an issue and concerned by Muslim’s consumers in Malaysia due to its uncertain Halal status on that product especially on non-Halal logo product certified by Department of Islamic Development Malaysia (JAKIM). Although the quantity of animal blood plasma consumption is low, its effect on the elasticity and structure of meatball are good. This study was conducted to detect the presence of chicken and porcine DNA in chicken meatballs by conventional polymerase chain reaction (PCR) assay targeted mitochondrial DNA (mtDNA) on chicken and short interspersed nuclear element (SINE) on porcine genome. Meatballs spiked with 1.0% (w/w) and 5.0% (w/w) porcine meat and gelatin, respectively, were prepared and heat-treated using five (n=5) cooking methods: boiling, pan-frying, roasting, microwaving and autoclaving. A pairs of mtDNA and SINE primers were targeted in short sequences using polymerase chain reaction (PCR) analysis, producing 129 and 161 bp amplicons, respectively. Electrophoresis analysis showed positive results for chicken and porcine DNA at 1.0% and 5.0% for both chicken meat and blood plasma for all of the different cooking techniques. In conclusion, in the presence study demonstrated the PCR analysis using species-specific primers was very useful for the detection of porcine DNA in heat-treated meatballs.